Actual Share Buybacks: Determinants and Price Effects - Rohaida, Abdul Latif (2010)
This thesis is prompted by the increasing number of Malaysian firms buying back their own shares on the open-market subsequent to the Asian financial crisis in late 1997. Studies on buybacks in Malaysia are very limited and have focused only on immediate price effects of buybacks. This study fills in the gap by i) examining the relevance of posited determinants of buyback decisions and ii)determining the shareholders' benefits by examining the price effects of buybacks in the announcement effects and in the long-run effects. The first part of the thesis examines the determinants of actual buyback decisions while the second part analyses the price effects of buyback activities(intentions and implementations) in immediate effects and in the long-run. The study examines all actual buyback firms that have purchased more than one percent of their ordinary shares cumulatively from 1999 to 2006. Implications stated in six hypotheses which are: i) signalling hypothesis, ii) free cash flow hypothesis, iii) optimal capital structure hypothesis, iv) dividend substitution hypothesis(DSH),v) stock liquidity hypothesis, and vi) management incentives hypothesis, are examined to see whether these could be supported in the context of actual buyback decisions in Malaysia. Three issues regarding the price impacts of buyback activities are analysed: i) price performance surrounding the announcement of buyback intentions, ii) price performance surrounding the announcement of buyback implementations and, iii) long-run price performance following buyback implementations. The findings suggest that signalling, liquidity, and management intention hypotheses are significant in explaining actual buyback decisions. This study indicates that actual buybacks were significantly induced by poor market performance, expectation of better future operating performance, poor prior stock liquidity level, nianagement of earnings, and desires to increase directors' control. The results for the immediate price effects indicate that the market is indifferent to announcement of buyback intentions but responds positively to buyback implementations. In the long-run, it is found that buyback firms do not experience significant price gains in the 3-year period following the implementation of buyback programs regardless of the benchmarks used (KLCI and matching-firms). This study contributes to the understanding of buybacks from the perspective of a developing country where most of the firms have concentrated ownership pattern and activities on buybacks are strictly regulated. Concentrated ownership could explain free cash flow hypothesis, dividend substitution hypothesis, earnings management and directors' control behaviour in buyback decisions.